Analysis of Synergistic Relationships Between Types of Actors in a Port System - Palominos-Villavicencio, F (Institute of Electrical and Electronics Engineers Inc., 2021)
This article deals with a study of the synergistic relationships between groups of public, private and social actors related to the operations of the port system. The results obtained are consistent, consistent with their expectations, do not present any type of atypical behavior and are logically explainable considering the type of interaction and company involved. Since synergy is present in those areas of the companies related to their strategic objectives, it is necessary to find a way to influence to introduce a greater degree of synergy in a natural way, which translates into an economic, social and environmental benefit, without forcing interactions, without introducing more bureaucratic relationships between the actors and without ideological biases, so that it has positive effects on the productive environment. Finally, it is recommended that any intervention in the system be carried out with the participation, agreements and commitments of all interested parties. © 2021 IEEE.